Perancangan Bangunan Mixed Use Al-Amin Living Lab Dan Industrial Park Di Desa Sampe Cita, Kecamatan Kutalimbaru - Novalinda, Novalinda; Wisdianti, Dara; Sigit, Faurantia Forlana; Akbar, Ivan Noor (Universitas Medan Area, 2024)
Mixed Use Building is the combination of buildings with different functions, a mix of residential, commercial, and cultural buildings planned within a city. This research focuses on the design of a Mixed Use building, referring to the process of planning, illustrating, and developing a concept or idea for a building or physical structure. The aim of this research is to understand the design of the Al-Amin Living Lab and Industrial Park Mixed Use Building in Sampe Cita Village, Kutalimbaru District. The research material is the site location in Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency, the needs of the academic community of Universitas Pembangunan Panca Budi regarding research land, and the potential development of the area as a tourist facility, in this case, a mall and other buildings that will support the activities of the area and the surrounding community. The results of this research explain that the facilities and infrastructure of the Al-Amin Living Lab and Industrial Park Mixed Use Building consist of a café, coffee shop, meeting room, viewing area, and toilets, and that the design direction for the Al-Amin Living Lab and Industrial Park Mixed Use Building has met the criteria.